2022
DOI: 10.3389/fnut.2022.911838
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Anti-breast Cancer Activity in vitro of a Novel Polysaccharide From Cymbopogon citratus

Abstract: Cymbopogon citratus is an important functional food, widely used for flavoring in Africa and South America. In this study, a novel high-molecular-weight polysaccharide (CCP) from C. citratus was extracted, and its structural characteristics and anti-breast cancer activity in vitro were investigated. CCP contained both α and β configurations and mainly composed of galactose (36.89%), arabinose (23.97%), glucose (18.35%) and rhamnose (9.36%) with an average molecular weight of 1.98 × 106 Da. The main glycosyl re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Unlike HWSPs, neither CCP nor CCF contains proteins, while CCP contains less uronic acid. Analysis of the monosaccharide composition by HPLC showed that CCP was composed of glucose, rhamnose, ribose, galactose, arabinose, xylose, and mannose, with a molar ratio of 6.17:5.90:3.40:2.92:2.31:1.63:1.00 ( Bao, Yuan, Wang, Fan, & Lan, 2015 , Chen et al, 2022 ). F1 and F2 are the polysaccharide fractions containing uronic acid.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Unlike HWSPs, neither CCP nor CCF contains proteins, while CCP contains less uronic acid. Analysis of the monosaccharide composition by HPLC showed that CCP was composed of glucose, rhamnose, ribose, galactose, arabinose, xylose, and mannose, with a molar ratio of 6.17:5.90:3.40:2.92:2.31:1.63:1.00 ( Bao, Yuan, Wang, Fan, & Lan, 2015 , Chen et al, 2022 ). F1 and F2 are the polysaccharide fractions containing uronic acid.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…This compound induced apoptosis of MDA-MB-231 cells by triggering the Fas/FasL-mediated death receptor pathway. Chen et al indicate that the results provide a theoretical basis for the use of C. citratus polysaccharide as a potential anti-breast cancer agent in functional foods and medicine [ 114 ].…”
Section: Anticancer Activity Of Cymbopogon Citratusmentioning
confidence: 99%
“…Moreover, CCPs could induce apoptosis of MDA-MB-231 cells by promoting the expression of FAS and FASL. 21 Water-soluble polysaccharides extracted from highland barley (BP-1) exhibited significant antiproliferative activity against human colorectal cancer cells HT-29 and induced cancer cell apoptosis in a caspase-dependent manner, which were mediated by ROS/JNK and NF-κB pathways. 22 Previous investigations indicated that the structural characteristics of dietary polysaccharides were closely linked to their anticancer properties.…”
Section: ■ Biological Functions Of Polysaccharidesmentioning
confidence: 99%
“…Cymbopogon citratus polysaccharides (CCPs) could significantly reduce the cell viability of human breast cancer MDA-MB-231 cells. Moreover, CCPs could induce apoptosis of MDA-MB-231 cells by promoting the expression of FAS and FASL . Water-soluble polysaccharides extracted from highland barley (BP-1) exhibited significant antiproliferative activity against human colorectal cancer cells HT-29 and induced cancer cell apoptosis in a caspase-dependent manner, which were mediated by ROS/JNK and NF-κB pathways .…”
Section: Biological Functions Of Polysaccharidesmentioning
confidence: 99%